2016
DOI: 10.15376/biores.11.4.8496-8508
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Microfibril Angles in Resonance and Non-Resonance Spruce Wood (Picea abies [L.] Karst.)

Abstract: Variation in microfibril angle (MFA) in the S2 of the tangent cell walls of resonance and non-resonance spruce wood (Picea abies [L.] Karst.) used in the manufacture of musical instruments was studied. MFA was measured directly after preliminary visualisation of microfibrils in the cell walls. In the tested samples the position of an annual ring in the samples had no significant influence on the MFA. In the resonance wood, MFA values were between two and three times smaller than in the nonresonance wood. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover the degree of cristallinity of the cellulose is also a source of variability. It has been higlighted in [14] that spruce tonewood exhibits a microfibril angle (MFA) that is two times lower than regular spruce. This study also showed that the MFA is smaller in latewood than in earlywood.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Moreover the degree of cristallinity of the cellulose is also a source of variability. It has been higlighted in [14] that spruce tonewood exhibits a microfibril angle (MFA) that is two times lower than regular spruce. This study also showed that the MFA is smaller in latewood than in earlywood.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…The power function with the exponent of nearly 2.7 for samples in class I may indicate a significant impact of the microfibril angle (MFA) on the modulus of elasticity. Hence, the wood density is not the only determinant of its mechanical properties, as reported earlier (Raczkowski 1965;Zhang 1997;Roszyk et al 2010;Krauss and Kúdela 2011;Roszyk et al 2012;Fabisiak and Mania 2016). The impact of MFA is particularly pronounced for the wood of higher density, i.e., in latewood with smaller MFA values.…”
Section: Resultsmentioning
confidence: 52%
“…Every type of wood exhibits specific variability along a radial cross-section, which impacts subsequent uses of the wood. Coniferous species usually exhibit an increase in density and mechanical properties from the core to the perimeter [ 37 , 38 , 39 ]. Conversely, in ring-porous species, the opposite trend is found [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%